Analysis of Domestic Resources Cost Based on Farm Typology of Bali Cattle in Plampang Sumbawa Regency, West Nusa Tenggara - Sudirman Sudirman; B. Hartono; I. Subagiyo; B. A. Nugroho (Tropical Animal Science Journal, 2018)
The objectives of the study were to analyze the use of Domestic Resources Cost based on the most prevalent typology of Bali cattle farm and to analyze the economic efficiency based on the typology of Bali cattle farm in Plampang Sub-district Sumbawa Regency, West Nusa Tenggara (NTB). The study was carried out in Plampang Sub-district, Sumbawa Regency in 2017, with 53 respondents selected randomly and the key respondents were head of farms UPT, extension workers, inter-island traders, agricultural equipment traders, as well as agricultural materials and medicines traders. The respondents were acquired by applying systematic random sampling based on the farm typology with survey method and analyzed by the analysis of Domestic Resource Cost and analysis of Policy Analysis Matrix. There were three most prevalent farm typologies of Bali cattle production system used by the farmers in Plampang Sub-district, Sumbawa Regency, West Nusa Tenggara. The most prevalent production systems were: a typology of 6 months grazed (June-November) and 6 months confined (December-May) which was called with an acronym as 66 typology, typology of tethered throughout the year called as tethered typology, and typology of confined throughout the years called as confined typology. Bali cattle comparative advantage based on the farm typology as shown by Domestic Resource Cost Ratio (DRCR) values were 0.28 in 66 typology, 0.48 in tethered typology, and 0.31 in confined typology. It means that to save Rp. 100 is required the domestic factor cost Rp. 28 of 66 typology; Rp. 48 of tethered typology, and Rp. 31 of confined typology. Thus, it can be concluded that if domestic beef from Bali cattle is produced domestically, it will save the foreign exchange as much as 72% of 66 typology; 54% of tethered typology; and 69% of confined typology based on the import costs that must be spent. The competitive advantage is shown by the PCR values of 0.32 in 66 typology, 0.46 in tethered typology, and 0.35 in confined typology.